2020
DOI: 10.1109/access.2019.2962521
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Critical Success Factors for Six Sigma in Higher Education Institutions: Development and Validation of a Surveying Instrument

Abstract: Critical success factors are key elements that enable the success of projects. This research work proposes the design and validation of an instrument to evaluate the implementation of six sigma critical success factors during improvement projects in higher education institutions. Eleven critical success factors were selected from the literature on the six sigma methodology, including managerial participation and commitment, six sigma linkage with the institutional strategy, six sigma linkage with suppliers, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 68 publications
2
16
0
Order By: Relevance
“…, the kurtosis values ranged from -0.948 to 7.423; hence, we confirmed that univariate normality was fulfilled in each variable. As for multivariable normality assumptions, multiple studies recommend Mardia's measure for multivariate kurtosis[61],[62],[72],[73]. Hence, we verified…”
supporting
confidence: 53%
See 2 more Smart Citations
“…, the kurtosis values ranged from -0.948 to 7.423; hence, we confirmed that univariate normality was fulfilled in each variable. As for multivariable normality assumptions, multiple studies recommend Mardia's measure for multivariate kurtosis[61],[62],[72],[73]. Hence, we verified…”
supporting
confidence: 53%
“…In turn, [95] proposed a survey instrument for TQM implementation and highlighted both process management and human resource involvement as the most important CSFs. In their work, Maciel-Monteon et al [62] described how cultural change, top management involvement and commitment, training and education, and linking SS with customers are the CSFs for SS implementation in higher education institutions. Finally, [48] found that employee involvement and management commitment are two of the CSFs for effective implementation of Lean Six Sigma (LSS) in SMEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A benefit is associated with a positive action or result that favors people and the organization [56], the benefit of implementing the LM methodology is reflected through a gradual reduction of activities and elements that do not add value to the organization [57].…”
Section: Benefits (B)mentioning
confidence: 99%
“…The scoring instrument developed in this study uses a five-point Likert scale, representing a range of perception from never (1) to always (5). The use of the five-point Likert scale in this type of operations management study is a popular option to measure latent variables through a set of related elements [72] [56].…”
Section: Waste Reductionmentioning
confidence: 99%